Oral Health in Medicine Model Curriculum: Edentulism and Complete Denture Care - Damian J. Lee; David A. Felton (Association of American Medical Colleges, 2012)
Abstract Edentulism is defined as the complete loss of all dentition, and it is a worldwide phenomenon. Edentulism ranges from 7% to 69% globally and 26% of US population between the ages of 65 years and 74 years are completely edentulous. Edentulism is associated with numerous consequences on overall health. According to World Health Organization criteria, edentulous patients are considered physically impaired due to the inability to eat and speak properly. Edentulous patients are associated with poor dietary habits and nutritional intake, osteoporosis, and increased risk of having hypertension and coronary artery disease. Literature has shown that edentulous patients are more likely to be smokers and have smoking-associated diseases such as asthma, emphysema, and cancer. Also, edentulism can affect the quality of life, where these patients tend to have unsatisfactory esthetics and lowered self-esteem. With the projection of increase in the number of elderly population with the "baby boomer" generation and demand for teeth replacements, it is vital that medical professionals become competent in understanding the consequences of edentulism on overall health, evaluating the oral conditions of the edentulous patients and have basic knowledge and understanding of complete denture care. This module includes a series of presentations that describe edentulous patients and complete dentures relationship, the oral structures of edentulous patients, and the complete denture fabrication process. The purpose of the resource is to introduce the medical professionals to edentulism and the associated morbidities associated with edentulism and denture wearing. The concept of using dental implants to provide retention for complete dentures is described, along with proper maintenance of complete dentures and oral hygiene instructions.